My home is my castle : exposition d'art contemporain. - Reding, Alex (Luxembourg : Dexia, 2006)
Aguirre y Otegui, Philip ; Arndt, Götz ; Balkenhol, Stephan ; Biwer, Jean-Marie ; Copers, Leo ; Damag ; Gaston ; Declercq, Alain ; Deroubaix, Damien ; François, Michel ; Gaillard, Frédéric ; Gillen, Tina ; Janssens, Ann Veronica ; Kiecol, Hubert ; Kippenberger, Martin ; Koberstädt, Seb ; Lévêque, Claude ; Massinon, Jeanchristophe ; Mechita, Myriam ; Ney, Moritz ; Panamarenko ; Quetsch, Roland ; Smati, Assan ; Swennen, Walter ; Tayou, Pascale Marthine ; Vilmouth, Jean-Luc ; Wagner, Roger
Dexia BIL, Galerie L'Indépendance et Parc Heintz, Luxemburg, 01/06/2006-27/10/2006
boek